Building Coherent Text Worlds in Virginia Woolf’s Short Story “Solid Objects” - CREANGA, Oxana (Études Interdisciplinaires en Sciences humaines, 2020)
Abstract: The article delves into the text world theory, a cognitive- linguistic model of human discourse processing, and its application to the short story “Solid Objects” by Virginia Woolf. Drawing on an interdisciplinary approach, the essay seeks to collocate the traditional concepts of narrative perspective and coherence with newly researched reading–oriented principles in cognitive poetics, contextual frame theory and text world theory, in order to provide an explanation of understanding and interpretation processes applied to complex narratives, such as Virginia Woolf’s short fiction. Generalizing from the cognitive theory of text worlds, the study focuses on the comprehensive set of world building elements, perspective actualization processes, and narrative techniques that help readers solve the inconsistencies resulting from various mismatches between the narrative content and narrative form. Thus, the study of the textual means that help readers construct a coherent mental representation of the different levels of the world represented in the story and the markers of point of view aspects proffer an explanation of literary reading experience, such as the immersion of readers into literary worlds of fictional texts by assuming various spatio-temporal positions and adopting characteristics and attitudes, perceptions and beliefs represented in the text.